Osončenost stavbnega ovoja kot osnova za energetsko učinkovit razvoj stanovanjske zazidave - Šprah, Nataša (visokošolska dela, 2021)
Increasing the density of multifamily housing developments intensifies mutual shading of buildings, and thus limits the use of the most universally available source of energy % the sun. Reduced building insolation decreases the potential for active and passive use of solar energy and daylighting. This doctoral dissertation includes a study of the relationship between certain urban indicators % i.e. site coverage and floor area ratio (FAR), building typology, layout and orientation % and the insolation of buildings in multifamily housing developments. Solar irradiation and illumination on building facades were investigated with models, on the basis of the characteristics of contemporary multifamily housing developments with point and linear building typologies in Slovenia. The amounts of solar irradiation and illumination on the facades obtained with computer simulations were compared, and the influence of individual urban indicators on the insolation of the building facade was determined. In accordance with previous research, the analysis showed a significant influence of the density of residential developments, both site coverage and FAR. The influence of the typology of buildings on the irradiation and illumination on the facade is substantial, while the influence of the orientation and layout of the developments is moderate. We established the irradiation threshold, required to equate the energy balance between solar gains and heat losses through the glazed opening during the heating season. A comparison with the simulation-derived average values of solar irradiation on the facades of the central buildings of the models during the heating season showed that these values are higher in all examined scenarios. Daylighting proved to be the deciding factor for determining the maximum density of individual typologies and layouts of residential developments. The minimum values for daylighting of the facades were determined using the requirements of the SIST EN 17037 standard. The simulated average vertical daylight factor values (VDavg) were compared with the minimum VDavg values of the facade that enable sufficient daylighting of the deepest, lowest, one-sidedly daylit occupied spaces, designed according to the Slovenian legislation, and placed in the lowest level of the buildings. The calculated maximum densities of individual typologies, which are in some cases lower than those of the analyzed real-life multifamily housing developments, were summarized in the form of diagrams to serve as recommendations for designing sufficiently daylit multifamily housing developments with point and linear building typologies in the early stages of planning.
Keywords: Built Environment; civil engineering; daylighting; Disertacije; doctoral thesis; energijska učinkovitost; energy efficiency; Fasade; gradbeništvo; Grajeno okolje; Osončenost; osvetljevanje z dnevno svetlobo; residential developments; SIST EN 17037; solar potential; sončni potencial; sustainable urban planning; trajnostno urbanistično načrtovanje; večstanovanjska zazidava; vertical daylight factor; vertikalni faktor dnevne svetlobe